Emerging Prognostic Biomarkers in Testicular Germ Cell Tumors: Looking Beyond Established Practice - Chovanec, Michal; Albany, Costantine; Mego, Michal; Montironi, Rodolfo; Cimadamore, Alessia; Cheng, Liang (Frontiers in Oncology, 2018)
Testicular germ cell tumors (GCTs) are unique among solid cancers. Historically, this disease was deadly if progressed beyond the stage I. The implementation of cisplatin-based chemotherapy regimens has drastically changed the clinical outcome of metastatic testicular cancer. Several biomarkers were established to refine the prognosis by International Germ Cell Collaborative Group in 1997. Among these, the most significant were primary tumor site, metastatic sites, such as non-pulmonary visceral metastases and the amplitude of serum tumor markers -fetoprotein, -chorionic gonadotropin and lactate dehydrogenase. Since then, oncology exploded with various molecular biomarkers to further refine the prognosis and treatment of malignancies. However, the ability to predict the prognosis and treatment response in GCTs did not improve for many years. Clinical trials with novel targeting agents that were conducted in refractory GCT patients have proven to have negative outcomes. With the recent advances and developments, novel biomarkers emerge in the field of GCT oncology. This review article aims to summarize the current knowledge in the research of novel biomarkers in testicular GCTs.